The Joy of Food Play – Gender and Class in Men’s auto/biographical Accounts of Everyday Food-ways - Parsons, Julie M. (Kvinder, Køn & Forskning, 2017)
The Joy of Food Play – Gender and Class in Men’s auto/biographical Accounts of Everyday Food-ways: This article is informed by research that set out to investigate the relationship between individuals and their everyday food-ways using an auto/biographical research approach. The focus of this article centres on the notion of food ‘play’ rather than food ‘work’ as significant in the performance of a gendered cultural habitus, whereby men distanced themselves from notions of feminised domesticity and health discourses by resorting to both hegemonic masculinities and epicurean foodways. Despite a contemporary trend that emphasises fluidities across gender boundaries and shifting roles, the 75 respondents in the study that informs this article presented their food autobiographies as a type of transformation narrative heavily influenced by the continued intersectionalities of gender and class. Indeed, for the male respondents in this UK based study, a commitment to epicurean food-ways becomes a field for the performance of hegemonic masculinities with the gourmet food adventurer emerging from this culinary field coded elite and male. This raises questions with regards to cultural influences on everyday food-ways, as well as notions of what it means to be a gourmet, epicure, or food adventurer within a contemporary foodscape.